The Strategic Use of Private Quality Standards in Vertical Relations - Isabel Teichmann; Vanessa von Schlippenbach (Verein für Socialpolitik, 2010)
This paper highlights the strategic role of private quality standards in vertical relations. Considering two symmetric downstream firms that are exclusively supplied by a finite number of upstream firms, we show that there exist asymmetric equilibria in the downstream firms' quality requirements. While one downstream firm has an incentive to exaggerate her quality requirements to weaken her suppliers' outside options, the competitor's best response is to reduce her own quality requirements. The higher (lower) quality standard is set above (below) the social optimum. It turns out that the use of private quality standards induces a decrease in social welfare.
Keywords: L15; L42; Q13; 330; Private Quality Standards; Vertical Relations; Buyer Power; Food Supply Chain